1996
DOI: 10.1590/s0037-86821996000400003
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito canino em foco recente de leishmaniose tegumentar no Município de Sabará, região metropolitana de Belo Horizonte

Abstract: In 1992, a dog naturally infected with Leishmania was found in a periurban area of Sabará, state of Minas Gerais, where human cutaneous leishmaniasis had been previously described. The parasite was classified as Leishmania, subgenus Viannia, which L. braziliensis, the main species of parasite present in the southeast Brazil, also belongs. In order to assess the importance of the dog in the transmission cycle of the disease, a canine survey was undertaken. Six hundred thirty-one dogs were examined and the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
9
1
5
Order By: Relevance
“…This situation was also observed in the municipality of Vassouras, which was characterized by extensive internal migration, thereby impairing and sometimes preventing the localization of many patients due to constant changes of address, because of the search for work or for less expensive rents. In contrast to the reports of Passos et al (1996), Barbosa Santos et al (1998) and Barbosa et al (1999), symptomatic cases of canine cutaneous leishmaniasis did not necessarily accompany human disease in the present study. Santos et al (2005) observed a high prevalence of canine infection associated with low endemicity of the human disease in an urban area of the municipality of Paracambi, State of Rio de Janeiro, a finding that cast doubt on the importance of dogs in the transmission chain.…”
Section: Discussioncontrasting
confidence: 99%
“…This situation was also observed in the municipality of Vassouras, which was characterized by extensive internal migration, thereby impairing and sometimes preventing the localization of many patients due to constant changes of address, because of the search for work or for less expensive rents. In contrast to the reports of Passos et al (1996), Barbosa Santos et al (1998) and Barbosa et al (1999), symptomatic cases of canine cutaneous leishmaniasis did not necessarily accompany human disease in the present study. Santos et al (2005) observed a high prevalence of canine infection associated with low endemicity of the human disease in an urban area of the municipality of Paracambi, State of Rio de Janeiro, a finding that cast doubt on the importance of dogs in the transmission chain.…”
Section: Discussioncontrasting
confidence: 99%
“…Passos et al 13 realizaram um inquérito em cães no Município de Sabará, Belo Horizonte, obtendo soro prevalência para leishmaniose igual a 3,2% (20/617) pela RIFI, sendo que nenhum destes animais apresentou lesão sugestiva para LTA.…”
Section: Discussionunclassified
“…Similarly, the reported coincidence between households with ACL patients and the presence of infected dogs reflects the fact that humans and dogs are likely to be exposed in the same way to the sandfly vector, but is not evidence for dogs being a reservoir of disease. 68,70,80,92,99,104 Direct evidence for a reservoir role for dogs depends on the measurement of three parameters, which together determine the probability that a domestic dog population plays a significant role in ACL epidemiology: 108 1) the prevalence of ACL infections in dogs; 2) the biting rate of sandfly vectors on dogs; and 3) the infectiousness of ACL-infected dogs to sandfly vectors. Each of these parameters is examined in detail below.…”
Section: Can Dogs Be Incriminated As Reservoir Hosts Of Human Acl?mentioning
confidence: 99%
“…84,94,96,116 Similarly, indirect comparisons of sensitivity can also be made by comparing the results for all reported surveys using a specific diagnostic method (Table 2). 38,57,61,[68][69][70]72,73,76,77,80,81,82,84,85,89,90,92,[94][95][96][97][99][100][101]103, Due to their logistic convenience and relatively high sensitivity, serologic tests are the standard tools for identifying Leishmania-infected dogs (Table 2). However, difficulties associated with the interpretation of seroprevalence data are 1) serology is prone to nonspecific cross-reactions (false-positives), e.g., due to Trypanosoma cruzi infection; 136 2) there may be a delay between infection and seroconversion (i.e., a prepatent period); 110,112,113,[137][138][139] 3) a fraction of infected dogs may never seroconvert; 137,[140][141][142] and 4) seroconversion may not be permanent.…”
Section: Can Dogs Be Incriminated As Reservoir Hosts Of Human Acl?mentioning
confidence: 99%